The Influence of Public Information Disclosure and Service Quality on Public Satisfaction at The Mandala Public Health Center in Medan City - MARPAUNG, Tiar Vita Vera BR.; NASUTION, Dito Aditia Darma (PT Keberlanjutan Strategis Indonesia, 2025)
Public information disclosure and service quality are factors that can increase public satisfaction. The purpose of this study is to determine the effect of public information disclosure and service quality on public satisfaction at the Mandala Community Health Center (UPT Puskesmas) in Medan City. A sample of 45 respondents was taken using a saturated sampling technique or population sample. The method used in this study is the multiple linear regression analysis method with SPSS 23 software, obtaining a regression of Y = 2.709 + 0.970 + 0.102 + . Based on these results, it can be concluded that public information disclosure and service quality have a positive and significant effect on public satisfaction at the Mandala Community Health Center (UPT Puskesmas) in Medan City.